Modern Money Theory 101: A reply to critics - Éric Tymoigne; L. Randall Wray (Levy Economics Institute of Bard College, 2013)
One of the main contributions of Modern Money Theory (MMT) has been to explain why monetarily sovereign governments have a very flexible policy space that is unencumbered by hard financial constraints. Through a detailed analysis of the institutions and practices surrounding the fiscal and monetary operations of the treasury and central bank of many nations, MMT has provided institutional and theoretical insights about the inner workings of economies with monetarily sovereign and nonsovereign governments. MMT has also provided policy insights with respect to financial stability, price stability, and full employment. As one may expect, several authors have been quite critical of MMT. Critiques of MMT can be grouped into five categories: views about the origins of money and the role of taxes in the acceptance of government currency, views about fiscal policy, views about monetary policy, the relevance of MMT conclusions for developing economies, and the validity of the policy recommendations of MMT. This paper addresses the critiques raised using the circuit approach and national accounting identities, and by progressively adding additional economic sectors.
Keywords: B5; E10; E11; E12; E31; E42; E58; E6; F41; 330; Modern Money Theory; Price Stability; Full Employment; Financial Stability; Money